Building inclusive and empowering agrifood systems for resilience - Malapit, Hazel J.; Meinzen-Dick, Ruth S.; Quisumbing, Agnes R.; Zseleczky, Laura (Virginia Polytechnic Institute and State University, 2020)
Agricultural communities face a range of shocks from animal disease and crop pest outbreaks to natural disasters, political conflicts, and health crises such as COVID-19. Women are often particularly vulnerable to such shocks given constraints they face in terms of access to information, household decision-making power, control over assets and resources, time burdens, and more. Enabling agricultural producers to recover from shocks and mitigate the risks of future threats requires technologies, practices, and policies that ensure women’s participation and access to benefits but also their empowerment to make strategic life choices. Necessary steps toward more inclusive agrifood systems include 1) increasing women’s decision-making power and control over resources and assets within households and communities, 2) raising women’s voices in key processes such as market negotiations, research, and political processes, and 3) including and considering women’s needs and preferences in the design of programs and institutions. By building more inclusive and empowering agricultural production systems, communities can better withstand crises and bounce back stronger, with benefits not only for women but for all of society.